Hypnosis for Awake Surgery of Low-grade Gliomas: Description of the Method and Psychological Assessment. Issue 1 (January 2016) - Zemmoura, Ilyess; Fournier, Eric; El-Hage, Wissam; Jolly, Virginie; Destrieux, Christophe; Velut, Stéphane
Abstract : BACKGROUND: Awake craniotomy with intraoperative electric stimulation is a reliable method for extensive removal of low-grade gliomas while preserving the functional integrity of eloquent surrounding brain structures. Although fully awake procedures have been proposed, asleep-awake-asleep remains the standard technique. Anesthetic contraindications are the only limitation of this method, which is therefore not reliable for older patients with high-grade gliomas. OBJECTIVE: To describe and assess a novel method for awake craniotomy based on hypnosis. METHODS: We proposed a novel hypnosedation procedure to patients undergoing awake surgery for low-grade gliomas in our institution between May 2011 and April 2015. Surgical data were retrospectively recorded. The subjective experience of hypnosis was assessed by 3 standardized questionnaires: the Cohen Perceived Stress Scale, the Posttraumatic Stress Disorder Checklist Scale, the Peritraumatic Dissociative Experience Questionnaire, and a fourth questionnaire designed specifically for this study. RESULTS: Twenty-eight questionnaires were retrieved from 43 procedures performed on 37 patients. The Peritraumatic Dissociative Experience Questionnaire revealed a dissociation state in 17 cases. The Perceived Stress Scale was pathological in 8 patients. Two patients in this group stated that they would not accept a second hypnosedation procedure. The Posttraumatic Stress Disorder Checklist Scale revealed 1 case of posttraumatic stress disorder. Burr hole and bone flap procedures were the most frequently reported unpleasant events during opening (15 of 52 events). CONCLUSION: The main findings of our study are the effectiveness of the technique, which in all cases allowed resection of the tumor up to functional boundaries, and the positive psychological impact of the technique in most of the patients. ABBREVIATIONS: AAA, asleep-awake-asleep HGG, high-grade glioma LGG, low-grade glioma PCLS, Posttraumatic Stress Disorder Checklist Scale PDEQ, Peritraumatic Dissociative Experience Questionnaire PSS, Cohen Perceived Stress Scale PTSD, posttraumatic stress disorder Abstract : Supplemental Digital Content is Available in the Text.